2016
DOI: 10.1002/chem.201505001
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the Nature of ZnII−SiII Bonds

Abstract: A series of zinc(II) silylenes was prepared by using the silylene {PhC(NtBu)2 }(C5 Me5 )Si. Whereas reaction of the silylene with ZnX2 (X=Cl, I) gave the halide-bridged dimers [{PhC(NtBu)2 }(C5 Me5 )SiZnX(μ-X)]2 , with ZnR2 (R=Ph, Et, C6 F5 ) as reagent the monomers [{PhC(NtBu)2 }(C5 Me5 )SiZnR2 ] were obtained. The stability of the complexes and the Zn-Si bond lengths clearly depend on the substitution pattern of the zinc atom. Electron-withdrawing groups stabilize these adducts, whereas electron-donating gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…6,[20][21][22][23][24][25] We recently presented a pentamethylcyclopentadienyl (Cp*) substituted version [{PhC(NtBu) 2 } Si(C 5 Me 5 )] (Scheme 1) and explored its coordination behavior towards transition metals and its reactivity with chalcogens. [26][27][28] In these complexes, we always observed a 1,2-silicon shi of the silylene on the Cp*-ring.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…6,[20][21][22][23][24][25] We recently presented a pentamethylcyclopentadienyl (Cp*) substituted version [{PhC(NtBu) 2 } Si(C 5 Me 5 )] (Scheme 1) and explored its coordination behavior towards transition metals and its reactivity with chalcogens. [26][27][28] In these complexes, we always observed a 1,2-silicon shi of the silylene on the Cp*-ring.…”
Section: Introductionmentioning
confidence: 75%
“…Furthermore, due to its relatively high steric demand, the 1,2-silicon shi should be suppressed. [26][27][28][29] [{PhC(NtBu) 2 }Si(C 5 Me 4 H)] (1) was synthesized in a rational approach from [{PhC(NtBu) 2 }SiCl] and KCp 4 in good yields (89%, Scheme 2). In contrast to its analogue, Cp* substituted compound 1 is soluble in all common but halogenfree solvents.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…In some of our studies, we have also shown that late transition metals (Ni(II), Pd(II), and Pt(II)) may serve the role of a lone pair donor at hexacoordinate silicon, for example, in I and II (Chart 1) [5][6][7][8]. That kind of complexes with silicon as a lone pair acceptor in the coordination sphere of a transition metal (TM) thus complements TM silicon complexes with, e.g., silylene ligands, in which the Si atom is the formal lone pair donor, such as III, IV, and V [9][10][11][12][13], and the silyl complexes, in which the TM-Si bond is one out of four bonds to a tetravalent Si atom (e.g., VI, VII, VIII, and IX) [14][15][16][17][18]. In complex IX and some other compounds with group 9 metals [19][20][21][22], the 2-pyridyloxy (pyO) ligand was successfully utilized for stabilizing the TM-Si bond by forming two bridges over the heterodinuclear core.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the Si atom is located on a crystallographically imposed center of inversion, and therefore the asymmetric unit consists of a half molecule and the symmetry related sites (e.g., O1 and O1* at Si1) are trans to each other. Selected bond lengths (Å) and angles (deg) for 5 are as follows: Pd1-Cl1 2.290(1), Pd1-Cl2 2.303(1), Pd1-N1 2.028(2), Pd1-N2 2.036(2), Si1-O1 1.794(2), Si1-O2 1.760(2), Si1-O3 1.770(2), N1-Pd1-Cl1 175.93(7), N2-Pd1-Cl2 176.15(7), Cl1-Pd1-Cl2 91.60(3), Cl1-Pd1-N2 88.91(7), Cl2-Pd1-N1 87.65(7), and N1-Pd1-N2 92.10(9); for 6: Cu1-Cl1 2.238(1), Cu1-Cl2 2.256(2), Cu1-N1 2.008(4), Cu1-N2 1.990(4), Si1-O1 1.790(3), Si1-O2 1.770(3), Si1-O3 1.755(3), N1-Cu1-Cl1 153.97(12), N2-Cu1-Cl2 162.50(12), Cl1-Cu1-Cl2 93.69(5), Cl1-Cu1-N2 90.82(11), Cl2-Cu1-N1 90.31(12), and N1-Cu1-N2 93.03(16).…”
mentioning
confidence: 99%